STUDY OF ANTIDEPRESSANTS EFFECT OF KRATOM (MITRAGYNA SPECIOSA (KORTH.) HAVIL.) LEAVES EXTRACT IN MALE SWISS WEBSTER MICE - br Tarigan, selvianita
Depression is a neurological disorder that has a high prevalence. An alternative treatment mode can come from natural ingredient, and one of them is kratom (Mitragyna speciosa Korth.), which has been shown to have biological activity in the nervous system. This research aims to study the antidepressant activities of kratom ethanol extract in a mouse model of depression. A total of 25 mice were divided into 5 groups, namely a negative control, positive control (fluoxetine 5 mg/kgBB) and 3 groups treated with kratom leaves extract at 50, 100 and 200mg/kgBB. The depression level was measured using 5 parameters obtained through the open-field test (namely Tcenter, Tborder, Tperiphere and distance travelled) and the forced-swimming test (immobility time). At the end of the experiment, brain cortisol levels were measured. Mice in the 100 mg/kg extract treatment group had significantly lower immobility time than the control group. Mice in this group also showed a higher percentage of the middle zone occupation and a longer distance travelled, significantly different from controls. In mice treated with 100 mg/kg extract, cortisol level was significantly lower than controls. Kratom at 100mg/kg showed significant antidepressive effect in terms of Tcenter (average 6,92% ± 4,27% vs. 1,38% ± 1,96%), Tperiphery (80,02% ± 12,44% vs. 95.92% ± 5,58%), distance travelled (7.033,08 ± 1.541,85 cm vs. 3.860,98 ± 1.872,16 cm), and immobility time (98,89 ± 13,95 detik vs. 168,74 vs 26,62 detik).